EVALUASI PROGRAM DESA TANGGUHBENCANA(DESTANA) DI KABUPATEN WONOGIRI TAHUN 2025 - Rini Tri Wayuni; Neny Marlina (Journal of Politic and Government Studies, 2026)
Wonogiri Regency is an area with high disaster vulnerability, requiring efforts to strengthen community capacity through the Disaster Resilient Village (Destana) Program. This study aims to evaluate the implementation of the DestanaProgram and identify its inhibiting factors. This research uses a descriptive qualitative method with the CIPP (Context, Input, Process, Product) evaluation model. Data collection techniques includeinterviews,observation,anddocumentation. The results show that in the context aspect, the program is aligned with regional needs and supported by strong regulations. In theinputaspect, there are limitations in human resources, volunteer capacity, and budget allocation. In the process aspect, the program has been implemented but monitoringandevaluationremainadministrative.In the product aspect, the program has increased community awareness but has not fully achieved village independence in disaster management. The study concludes that the Destana Program has been implemented butisnotyetoptimal. Therefore, strengthening human resources, increasing budget support, and improving performance-based monitoring systems are necessary.